Isolation of Circulating Tumor Cells to Diagnose Melanoma and Evaluate the Efficacy of Surgical Resection Using Melanoma‐Specific Microsystem. Issue 8 (19th April 2022) - Kang, Yoon-Tae; Mutukuri, Anusha; Hadlock, Thomas; Fairbairn, Heather; Carle, Taylor R.; Fouladdel, Shamileh; Murlidhar, Vasudha; Kramer, Aaron; Reguera, Monica De Silva; Azizi, Ebrahim; Durham, Alison; Mclean, Scott A.; et al.
Abstract : Melanoma is one of the most aggressive skin cancers due to its potential to metastasize widely in the body. The risk of metastasis is increased with later detection and increased thickness of the primary lesion, thus early identification/surgical removal is critical for higher survival rates. Recent advances in liquid biopsy have proposed less‐invasive alternatives for cancer diagnosis and monitoring using minimal invasion at sample collection, and circulating tumor cells (CTCs) have been considered a promising blood‐based surrogate marker of primary tumors. Herein, the melanoma‐specific OncoBean platform (MelanoBean) conjugated with melanoma specific antibodies is used. From the comprehensive studies based on change in the number and characteristics of CTCs/CTCs‐clusters pre‐ and post‐surgical treatment, this work demonstrates that melanoma patients ( n = 45) at all stages (I–IV) have a noticeable number of CTCs as well as CTC‐clusters compared to healthy donors ( n = 9) ( p = 0.0011), and surgical treatment leads to a significant decrease in the CTC number ( p < 0.0001). The CTCs recovered from the device undergo molecular profiling for melanoma‐associated genes expression using multiplexed qRT‐PCR, demonstrating the ability to monitor molecular signature through treatment. The presented MelanoBean and the comprehensive approach will empower prognostic value of CTCs in melanoma in much larger cohort studies. Abstract : Melanoma is one of the most aggressive skin cancers and risk of metastasis is increased with later detection/increased primary lesion thickness, thus surgical removal is critical for higher survival rates. Herein microfluidic platform is devised for diagnosing melanoma and evaluating surgical efficacy based on change in the number and characteristics of circulating tumor cells (CTCs)/CTC clusters pre‐ and post‐surgical treatment.